Efektivitas Kredibilitas Bank Sentral terhadap Inflasi bagi Produsen dan Konsumen di Indonesia - Prabowo, Rakhmat; Ikhsan, Mohamad (UI Scholars Hub, 2020)
This study is intended to explain the impact of central bank credibility on inflation in Indonesia at the producer and consumer level. In this study, Central Bank Credibility is measured using an index with values between 0 (zero credibility) and 1 (perfect credibility). Generalized Method of Moments (GMM) method is used to analyze the impact of central bank credibility on inflation. Based on the results, central bank credibility can reduce inflation on both producer and consumer price. Central bank credibility is more sensitive towards producer price index compared to Gross Domestic Product (GDP) deflator and wholesale price index while at the consumer level, central bank credibility is more sensitive towards core inflation compared to headline inflation.